Quality control during repeated fryings - C. Cuesta; F. J. Sánchez-Muniz (Grasas y Aceites, 1998)
Most of the debate ¡s about how the slow or frequent turnover of fresh fat affects the deterioration, of fat used in frying. Then, the modification of different oils used in repeated fryings of potatoes without or with turnover of fresh oil, under similar frying conditions, was evaluated by two criteria: by measuring the total polar component isolated by column chromatography and by the evaluation of the specific compounds related to thermoxidative and hydrolytic alteration by High Performance Size Exclusion Chromatography (HPSEC). The results indicate that with frequent turnover of fresh oil, the critical level of 25% of polar material is rarely reached, and there are fewer problems with fat deterioration because the frying tended to increase the level of polar material and thermoxidative compounds (polymers and dimers of triglycerides and oxidized triglycerides) in the fryer oil during the first fryings, followed by minor changes and a tendency to reach a near-steady state in successive fryings. However, in repeated frying of potatoes using a null turnover the alteration rate was higher being linear the relationship found between polar material or the different thermoxidative compounds and the number of fryings. On the other hand chemical reactions produced during deep-fat frying can be minimized by using proper oils. In addition the increased level of consumers awareness toward fat composition and its impact on human health could had an impact on the selection of fats for snacks and for industry. In this way monoenic fats are the most adequate from a nutritional point of view and for its oxidative stability during frying.